Transient response to imatinib in a chronic eosinophilic leukemia associated with ins(9;4)(q33;q12q25) and a CDK5RAP2-PDGFRA fusion gene - Walz, Christoph; Curtis, Claire; Schnittger, Susanne; Schultheis, Beate; Metzgeroth, Georgia; Schoch, Claudia; Lengfelder, Eva; Erben, Philipp; Müller, Martin Christian; Haferlach, Torsten; Hochhaus, Andreas; Hehlmann, Rüdiger; et al. (Genes, chromosomes & cancer, 2006)
Chronic myeloproliferative disorders with rearrangements of the platelet-derived growth factor receptor A (PDGFRA) gene at chromosome band 4q12 have shown excellent responses to targeted therapy with imatinib. Here we report a female patient who presented with advanced phase of a chronic eosinophilic leukemia. Cytogenetic analysis revealed an ins(9;4)(q33;q12q25) in 5 of 21 metaphases. FISH analysis with flanking BAC probes indicated that PDGFRA was disrupted. A novel mRNA in-frame fusion between exon 13 of the CDK5 regulatory subunit associated protein 2 (CDK5RAP2) gene, a 40-bp insert that was partially derived from an inverted sequence stretch of PDGFRA intron 9, and a truncated PDGFRA exon 12 was identified by 5′-RACE-PCR. CDK5RAP2 encodes a protein that is believed to be involved in centrosomal regulation. The predicted CDK5RAP2-PDGFRA protein consists of 1,003 amino acids and retains both tyrosine kinase domains of PDGFRA and several potential dimerization domains of CDK5RAP2. Despite achieving complete cytogenetic and molecular remission on imatinib, the patient relapsed with imatinib-resistant acute myeloid leukemia that was characterized by a normal karyotype, absence of detectable CDK5RAP2-PDGFRA mRNA, and a newly acquired G12D NRAS mutation. © 2006 Wiley-Liss, Inc.